2023
DOI: 10.3390/cancers15102832
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Standardized Outcomes for Surgical Salvage of HPV-Positive Recurrent Oropharyngeal Squamous Cell Carcinoma: A Systematic Scoping Review

Abstract: Although HPV status is known to provide an improved prognosis in initial treatments of HPV-positive oropharyngeal squamous cell carcinoma (OPSCC), it is unclear how it affects patients who receive salvage surgery (SS), which has historically poor survival rates. The purpose of this study was to evaluate the role of SS for patients with locoregional recurrence (LRR) of HPV-positive OPSCC and its impact survival rates. We conducted a scoping review of literature through October 2022 and included 995 individuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Reported 3-year survival rates following salvage surgery for oropharyngeal carcinoma ranged from 34 to 62% [45,46]. In the study by Zafereo et al, twenty-six out of thirty-nine patients (67%) developed a second recurrence after salvage surgery for oropharyngeal cancer [47].…”
Section: Salvage Surgery: Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported 3-year survival rates following salvage surgery for oropharyngeal carcinoma ranged from 34 to 62% [45,46]. In the study by Zafereo et al, twenty-six out of thirty-nine patients (67%) developed a second recurrence after salvage surgery for oropharyngeal cancer [47].…”
Section: Salvage Surgery: Survivalmentioning
confidence: 99%
“…Patients with recurrent neck disease (p = 0.01) and positive surgical margins (p = 0.04) experienced higher rates of recurrence after salvage surgery. For HPV-related oropharyngeal cancer, Taniguchi et al found heterogeneity when reporting overall and disease-specific survival outcomes after salvage surgery [45]. Two-year overall survival, specifically after salvage surgery for HPV-related oropharyngeal carcinoma, was reported at 51% in one study [48] and 91% in another [49], and 5-year overall survival was reported at 27% in one study [48] and 43% in another [50].…”
Section: Salvage Surgery: Survivalmentioning
confidence: 99%
“…Salvage surgery exists in case of recurrent or persistent disease after initial definitive treatment [ 17 , 18 ]. Unfortunately, these patients have historically poor survival outcomes, and the impact of HPV positivity has not been well established due to a lack of reported survival characteristics in patients that undergo salvage surgery (see the article by Taniguchi in this issue) [ 19 ]. The need for future research into survival measures in these patients is needed.…”
mentioning
confidence: 99%